Thermodynamic study of the thallium-thulium tellurides by EMF method - Imamaliyeva, S.Z.; Mekhdiyeva, I.F.; Jafarov, Y.I.; Babanly, M.B. (KU Publ., 2021)
In this study the phase equilibria in the Tl2Te–Tl2Te3–TlTmTe2 compositions area of the Tl–Tm–Te ternary system were studied by powder X-ray diffraction (PXRD) analysis. Based on PXRD data, the solid-phase equilibria diagram was plotted. The thermodynamic functions of the Tl9TmTe6 and TlTmTe2 ternary compounds were calculated by the electromotive forces method. The electrochemical cells of the following type (−) TmТе (s.) | glycerol + KCl + TmCl3 | (Tm in alloys of Tl–Tm–Te system) (s.) (+) were assembled and their EMF were measured in the 300-450 K temperature range. Based on obtained EMF data for the Tl2Te3–TlTe– TlTmTe2 and TlTe–TlTmTe2–Tl9TmTe6 three-phase regions, the relative partial thermodynamic functions of TmTe in alloys were calculated. The combination of these functions with the partial molar functions of thulium in TmTe allowed calculating the corresponding partial functions of thulium in the above phase regions. The potential-forming reactions responsible for the indicated partial molar values were obtained based on constructed solid-phase equilibria diagram. Using indicated potential-forming reactions, for the first time, the standard thermodynamic functions of formation and standard entropies of the Tl9TmTe6 and TlTmTe2 compounds were calculated.
Талий-тулий теллуридтерін ЭҚК әдісімен термодинамикалық зерттеу
Термодинамическое исследование теллуридов талия-тулия методом ЭДС
Keywords: Tl–Tm–Te system; Tl9TmTe6; TlTmTe2; powder X-ray diffraction analysis; solid-phase equilibria diagram; method of electromotive forces; concentration cells; thermodynamic functions